Analysis of Gallbladder Stones by X-ray Fluorescence - Saeed, Mustafa Safaa Abdul Jabbar; Jomea, Zaid Mohammed Abd Zaid; Mohammed, Ahmed Yahea Jassim; Neama, Ruaa Abdullah Yousif (Central Asian Journal of Medical and Natural Science, 2025)
Gallstone disease impacts millions globally. Over the decades modern techniques have been applied in laminar. Nevertheless, the fundamental cause of its formation has continued to be a topic of speculation. The current analysis of present sunshine utilizes various methods, including infrared. Through FTIR spectroscopy, we investigated the role of cholesterol, bilirubin, and calcium carbonate in gallstone formation within the gallbladder. Our experimental findings indicated that cholesterol, whether alone or in conjunction with bilirubin and calcium carbonate, is the predominant component of human gallstones and serves as the primary cause of gallstone formation. Gallstone samples were identified using WDXRF. Some of the interiors exhibited tones of pebbles in various colors, while the outer casing was brown and black. FTIR analyses are presented, along with WD-XRF analyses and other findings related to gallstone samples. This clearly demonstrates that calcium and copper constitute the salts of bilirubin's to a greater extent than the brown and black coloration of the central part of gallstones